Effect of CpG methylation on RAG1/RAG2 reactivity: implications of direct and indirect mechanisms for controlling V(D)J cleavage - Nakase, Hiroshi (2003)
It has been suggested that DNA methylation/demethylation is involved in regulating V(D)J rearrangement. Although methylated DNA is thought to induce an inaccessible chromatin structure, it is unclear whether DNA methylation can directly control V(D)J recombination independently of chromatin structure. In this study, we tested whether DNA methylation directly affects the reactivity of the RAG1/RAG2 complex. Specific methylation within the heptamer of the recombination signal sequences (RSS) markedly reduced V(D)J cleavage without inhibiting RAG1/RAG2–DNA complex formation. By contrast, methylation at other positions around the RSS did not affect the reactivity of the RAG proteins. The presence of a methyl-CpG binding-domain protein inhibited the binding of the RAG1/RAG2 complex to all the methylated CpG sites that were tested. Our findings suggest that DNA methylation around the RSS may have a previously unexpected function in regulating V(D)J recombination by directly inhibiting V(D)J cleavage, in addition to its general function of inducing an inaccessible chromatin configuration.